PENGARUH PENDIDIKAN KESEHATAN MENGGUNAKAN MEDIA KARTU TRUTH OR DARE TERHADAP PENGETAHUAN DAN SIKAP CUCI TANGAN PAKAI SABUN (CTPS) PADA SISWA SEKOLAH DASAR (Politeknik Kesehatan Kemenkes Bandung, 2023)
Hand washing with soap is important to help reduce the incidence of diarrhea by 47%, prevent transmission of Covid-19 and reduce Acute Respiratory Infections (ARI) by 20%. Indonesian people's awareness of washing hands with soap is still low, based on the results of Riskesdas in 2018, the population aged 10 years who behaved in washing their hands properly was 49.8%. School-age children are at an age prone to disease, generally school-age children do not really understand the cleanliness of their bodies. One of the health behavior problems in school-age children is related to not applying the habit of washing hands with soap. The purpose of the study was to determine the effect of health education using the truth or dare on increasing knowledge and attitudes of washing hands with soap (CTPS) on Kiangroke 02 State Elementary School Students. The research method used is a pre-experiment using One Group Pretest – Posttest Design. The research population of grade 4 students was 81 people with a sample of 45 people, using the proportional stratified random sampling technique. The analysis uses the Wilcoxon to prove the research hypothesis. Results This research was obtained through the results of the pretest and posttest of knowledge and attitudes showed the p value of knowledge was (0.000 < 0.05) and p value of attitude was (0.002 < 0.05). So it can be concluded that there is an effect of health education using truth or dare card on knowledge and attitude of Washing Hands with Soap (CTPS) on Kiangroke State Elementary School Students 02. Key words : Truth or dare Card, Health Education, Handwashing with Soap, Knowledge, Attitude